Exploring different social media users from the millennials’ generation: a cross-cultural behavioral analysis of Brazilian users of Facebook and chinese users of RenRen - Park, Bruno (2015)
With the increasing importance of digital communication and its distinct characteristics, marketing tools and strategies adopted by companies have changed dramatically. Among the many digital marketing tools and new media channels available for marketers, the phenomenon known as social media is one of the most complex and enigmatic. It has a range that still is quite unexplored and deeply transforms the present view on the promotion mix (Mangold & Faulds, 2009). Conversations among users on social media directly affect their perceptions on products, services and brands. But more than that, a wide range of other subjects can also become topics of conversations on social media. Hit songs, sporting events, celebrity news and even natural disasters and politics are topics that often become viral on the web. Thus, companies must grasp that, and in order to become more interesting and relevant, they must take part in these conversations inserting their brands in these online dynamic dialogues. This paper focuses on how these social interactions are manifested in the web in to two distinct cultures, Brazil and China. By understanding the similarities and differences of these cultures, this study helps firms to better adjust its marketing efforts across regions, targeting and positioning themselves, not only geographically and culturally, but also across different web platforms (Facebook and RenRen). By examining how companies should focus their efforts according to each segment in social media, firms can also maximize its results in communication and mitigate risks. The findings suggest that differences in cultural dimensions in these two countries directly affect their virtual social networking behavior in many dimensions (Identity, Presence, Relationships, Reputation, Groups, Conversations and Sharing). Accordingly, marketing efforts must be tailored to each comportment and expectations.